Digital Native Generation: Teachers' Challenges in Building National Character in the Digital Era - Widiatmaka, Pipit; Nuryadi, Muhammad Hendri; Rochsantiningsih, Dewi; Gunarhadi (Universitas Pancasakti Tegal, 2025)
The purpose of this study is to investigate the strategies teachers use to foster nationalism in the digital native generation, as well as the challenges they face in fostering nationalism in this generation. This research uses a qualitative approach and a type of literature research. The data collection technique with document study and data analysis used is content analysis. The strategy to build the character of the native generation nationalism in the digital era is that teachers must be able to master their competencies as educators, prepare effective learning tools, and be able to implement a variety of learning methods and be able to utilize digital-based learning media. Teachers in building the character of nationalism in the digital native generation have several obstacles, especially there are still many teachers who have not been able to master some competencies as an educator (pedagogic and personality). In addition, they have also not been able to implement varied learning methods and have not been maximized in utilizing digital-based learning media.